2019
DOI: 10.5194/aab-62-605-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype and fattening system on the quality of male lamb meat – Part 1: Technological properties and carcass measurements

Abstract: Abstract. This study was conducted to determine the effect of genotype and fattening system on carcass measurements of lambs and technological properties of the male lamb meat (Musculus longissimus dorsi, MLD). The animal material in the study included 39 Hemşin (H) and 39 Tuj (T) male lambs. Extensive (E), semi-intensive (SI) and intensive (I) fattening systems were applied in the study, which was completed within 90 d. In the E, SI and I fattening groups, a total of 48 lambs, including 16 lambs in each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Fatty acid composition influences the nutritive value and organoleptic traits of meat including tenderness, flavor, and juiciness [20]. The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid composition influences the nutritive value and organoleptic traits of meat including tenderness, flavor, and juiciness [20]. The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The values of the expressed juice for LL and ST muscles indicate that the meat of PW lambs has a better ability to hold its own water compared to PL sheep. The influence of the genotype on water-holding capacity (WHC) was also confirmed in the research by Sarı et al (2019) conducted on Turkish sheep breeds. Also, Souza et al (2016) found that meat from Santa Inez lambs had a lower WHC than Dorper crossbreeds.…”
Section: Resultsmentioning
confidence: 69%
“…Sheep are grazing animals that get most of their nutrient requirements from pasture. They are more economical than other animal species, are resistant to diseases and harsh environmental conditions, are easy to herd, and can effectively benefit from plant resources (Sarı et al, 2019).…”
Section: Introductionmentioning
confidence: 99%